A new method of measuring centre-of-mass velocities of radially pulsating stars from high-resolution spectroscopy. Issue 3 (19th December 2017) - Britavskiy, N; Pancino, E; Tsymbal, V; Romano, D; Fossati, L
Abstract: We present a radial velocity analysis of 20 solar neighbourhood RR Lyrae and three Population II Cepheid variables. We obtained high-resolution, moderate-to-high signal-to-noise ratio spectra for most stars; these spectra covered different pulsation phases for each star. To estimate the gamma (centre-of-mass) velocities of the programme stars, we use two independent methods. The first, 'classic' method is based on RR Lyrae radial velocity curve templates. The second method is based on the analysis of absorption-line profile asymmetry to determine both pulsational and gamma velocities. This second method is based on the least-squares deconvolution (LSD) technique applied to analyse the line asymmetry that occurs in the spectra. We obtain measurements of the pulsation component of the radial velocity with an accuracy of ±3.5 km s −1 . The gamma velocity was determined with an accuracy of ±10 km s −1, even for those stars having a small number of spectra. The main advantage of this method is the possibility of obtaining an estimation of gamma velocity even from one spectroscopic observation with uncertain pulsation phase. A detailed investigation of LSD profile asymmetry shows that the projection factor p varies as a function of the pulsation phase – this is a key parameter, which converts observed spectral line radial velocity variations into photospheric pulsation velocities. As a by-product of our study, we present 41 densely spaced synthetic grids of LSD profile bisectors based on atmospheric models of RR Lyr covering all pulsation phases.